(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Viral infection has made the world to pass through the most critical time of the current century. In December 2019, the Wuhan city of China faced a novel etiological viral agent with atypical secondary pneumonia. The unique virus was severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that caused coronavirus disease 2019 (COVID-19) pandemic. According to the worldometer data, as of December 24, 2020, the world lost more than 1.74 million lives and infected more than 79.3 million people with the novel coronavirus-2. As there is no approved drug to combat the disease or vaccine against the virus, the infection continuously triumphed over the current medical system. The epidemiological analysis showed that geriatric patients are generally the most susceptible to the viral infection, and pediatric patients exhibited milder complications. The clinical characteristics of COVID-19 displayed that the most frequent symptoms are dry cough, fever, dyspnea, and sputum production. Herd immunity is a tested strategy that could moderate viral transmission in developing countries. In this study, authors abridged the epidemiological outcomes, clinical features, and pathophysiology of SARS-CoV-2 infection. The article also focused on vaccine development, herd immunity, and the most promising repurposed therapeutics for the treatment of COVID-19 with their clinical trial updates. Bangladesh Pharmaceutical Journal 24(1): 61-75, 2021